Depletion-induced interactions modulate nanoscale protein diffusion in polymeric crowder solutions - Michelle Dargasz; Nimmi Das Anthuparambil; Sebastian Retzbach; Anita Girelli; Sonja Timmermann; Johannes Möller; Wonhyuk Jo; Aliaksandr Leonau; Mohammad Raza Agha; Maddalena Bin; Jaqueline Savelkouls; Iason Andronis; et al. (Proceedings of the National Academy of Sciences, 2026)
Macromolecular crowding plays a crucial role in modulating protein dynamics in cellular and in vitro environments. Polymeric crowders such as dextran and Ficoll are known to induce entropic forces, including depletion interactions, that promote structural organization, yet their nanoscale consequences for protein dynamics remain poorly understood. Here, we employ megahertz X-ray photon correlation spectroscopy (MHz-XPCS) at the European X-ray Free Electron Laser (XFEL) to probe the dynamics of the protein ferritin in solutions containing sucrose, dextran, and Ficoll. We find pronounced changes in collective protein dynamics in polymeric crowders, revealing depletion-driven short-range attractions that, combined with long-range repulsions, give rise to intermediate-range organization. These mesoscale correlations undergo collective relaxation on microsecond to millisecond timescales, as directly resolved by XPCS through the decay of ferritin density fluctuations. The magnitude of this depends sensitively on crowder molecular weight and type. Normalizing the crowder concentration by c * reveals scaling behavior of ferritin self-diffusion with a crossover near 2 c *, marking a transition from depletion-enhanced mobility to viscosity-dominated slowing. Our results demonstrate that bulk properties alone are insufficient to describe protein dynamics in crowded solutions, highlighting the need to include polymer-specific interactions and depletion theory in models of crowded environments.